Hydrobiogechemical interactions in the hyporheic zone of a sulfate-impacted, freshwater stream and riparian wetland ecosystem. Issue 9 (6th June 2022) - Torgeson, Joshua M.; Rosenfeld, Carla E.; Dunshee, Aubrey J.; Duhn, Kelly; Schmitter, Riley; O'Hara, Patrick A.; Ng, G. H. Crystal; Santelli, Cara M.
Abstract : Biogeochemical cycling of S, Fe, and C in the hyporheic zone is influenced by dynamic hydrologic conditions. Abstract : Coupled abiotic and biotic processes in the hyporheic zone, where surface water and groundwater mix, play a critical role in the biogeochemical cycling of carbon, nutrients, and trace elements in streams and wetlands. Dynamic hydrologic conditions and anthropogenic pollution can impact redox gradients and biogeochemical response, although few studies examine the resulting hydrobiogeochemical interactions generated within the hyporheic zone. This study examines the effect of hyporheic flux dynamics and anthropogenic sulfate loading on the biogeochemistry of a riparian wetland and stream system. The hydrologic gradient as well as sediment, surface water, and porewater geochemistry chemistry was characterized at multiple points throughout the 2017 spring-summer-fall season at a sulfate-impacted stream flanked by wetlands in northern Minnesota. Results show that organic-rich sediments largely buffer the geochemical responses to brief or low magnitude changes in hydrologic gradient, but sustained or higher magnitude fluxes may variably alter the redox regime and, ultimately, the environmental geochemistry. This has implications for a changing climate that is expected to dramatically alter the hydrological cycle. Further, increased sulfate loading and dissolved or adsorbed ferric iron complexes in the hyporheic zone may induce a cryptic sulfur cycle linked to iron and carbon cycling, as indicated by the abundance of intermediate valence sulfur compounds ( e.g., polysulfide, elemental sulfur, thiosulfate) throughout the anoxic wetland and stream-channel sediment column. The observed deviation from a classical redox tower coupled with potential changes in hydraulic gradient in these organic-rich wetland and stream hyporheic zones has implications for nutrient, trace element, and greenhouse gas fluxes into surface water and groundwater, ultimately influencing water quality and global climate.